2020
DOI: 10.3389/fpls.2020.00467
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Genetics of a Sorghum bicolor × S. halepense Backcross Populations

Abstract: Despite a "ploidy barrier," interspecific crosses to wild and/or cultivated sorghum (Sorghum bicolor, 2n = 2x = 20) may have aided the spread across six continents of Sorghum halepense, also exemplifying risks of "transgene escape" from crops that could make weeds more difficult to control. Genetic maps of two BC 1 F 1 populations derived from crosses of S. bicolor (sorghum) and S. halepense with totals of 722 and 795 single nucleotide polymorphism (SNP) markers span 37 and 35 linkage groups, with 2-6 for each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 45 publications
1
13
1
Order By: Relevance
“…These maps respectively span 37 and 35 linkage groups, with 2-6 for each of the 10 basic sorghum chromosomes due to fragments covering different chromosomal portions or independent segregation from different S. halepense homologs. Details of population development, genotyping methods and methods for QTL analysis were discussed in Kong, Nabukalu [29] and [30].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These maps respectively span 37 and 35 linkage groups, with 2-6 for each of the 10 basic sorghum chromosomes due to fragments covering different chromosomal portions or independent segregation from different S. halepense homologs. Details of population development, genotyping methods and methods for QTL analysis were discussed in Kong, Nabukalu [29] and [30].…”
Section: Methodsmentioning
confidence: 99%
“…To fully utilize the available data while protecting against false-positive results, genetic analysis employed two approaches. Using genetic maps that were constructed as described [29] from selected well-groomed SNP segregation data for each of the two SBSH-BC 1 F 2 populations, interval mapping was conducted [33]. Permutation tests (with α = 0.10) suggested LOD scores of 2.9 and 3.1 for H4 and H6 populations, respectively.…”
Section: Genetic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Genotyping and linkage map construction were reported previously (Kong et al 2020). Briefly, genotypes were determined by single nucleotide polymorphism (SNP) 'calling' based on the reference genome of S. bicolor BTx623 v1.4 (Paterson et al 2009), using Tassel-GBS 5 (Glaubitz et al 2014).…”
Section: Qtl Analyses and Detectionmentioning
confidence: 99%
“…While Paterson et al (1995) reported that S. halepense contained restriction fragment length polymorphisms (RFLPs) specific to S. propinquum and S. bicolor, they also identified S. halepense specific alleles. More recent studies have shown introgression of S. halepense alleles to S. bicolor in crop : weed hybridization events (Kong et al, 2020;Morrell et al, 2005), confounding the determination of S. halepense evolutionary origins from genomic data alone. Collectively, these molecular findings suggest that S. halepense is either a derivative from hybridization between S. bicolor and S. propinquum or an unknown, but closely related Sorghum species with increased homology due to cumulative introgression events over evolutionary time periods.…”
Section: Meiotic Chromosome Behaviormentioning
confidence: 99%